2017
DOI: 10.3399/bjgp17x691685
|View full text |Cite
|
Sign up to set email alerts
|

The role of contraindications in prescribing anticoagulants to patients with atrial fibrillation: a cross-sectional analysis of primary care data in the UK

Abstract: The presence or absence of recorded contraindications has little influence on the decision to prescribe anticoagulants for the prevention of stroke in patients with AF. The study analysis suggests that, nationally, 38 000 patients with AF with contraindications are treated with anticoagulants. This has implications for patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, when ineligible patients include those with contraindications, the proportion of ineligible patients prescribed anticoagulants was greater and increased from 28.1% (95% CI 26.3% to 29.9%) in 2000 to 47.5% (95% CI 46.1 to 48.9) in 2016, p<0.001 (online supplementary figure 2, online supplementary table 5); this is driven by treatment of patients with AF with contraindications 23…”
Section: Resultsmentioning
confidence: 99%
“…However, when ineligible patients include those with contraindications, the proportion of ineligible patients prescribed anticoagulants was greater and increased from 28.1% (95% CI 26.3% to 29.9%) in 2000 to 47.5% (95% CI 46.1 to 48.9) in 2016, p<0.001 (online supplementary figure 2, online supplementary table 5); this is driven by treatment of patients with AF with contraindications 23…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, primary care physicians achieve lower anticoagulation rates compared with hospital-based physicians 28 29. While there are multiple reasons for these differences, which include differences in populations, with high percentage of (relative) contraindications (40%–65%) and care-related factors, the lack of an integral decision tool impedes informed decisions on initiating or continuing antithrombotic therapy 10 30…”
Section: Discussionmentioning
confidence: 99%
“…This figure would chime with the observation from primary care’s Quality Outcomes Framework data that about 6% of the overall AF cohort in the UK are deemed to have contraindications to anticoagulation, although this was lower than the estimated 12% from the US. [ 14 , 15 ] Furthermore, the SSNAP data showed that 2,705 strokes occurred in AF patients who were already receiving anticoagulation therapy (12.3% of the total cohort).…”
Section: Demand For Left Atrial Appendage Occlusion In the Ukmentioning
confidence: 99%